ANALISIS KESULITAN SISWA DALAM PENERAPAN WUDHU PADA PEMBELAJARAN FIKIH DI MTs.S GERPEMI TEBAS TAHUN PELAJARAN 2024-2025 - Irwansyah; Susilawati; Elsa Mulya Karlina (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This thesis aims to describe the phenomena related to students’ difficulties in performing wudhu (ablution) in fiqh learning at MTs.S Gerpemi Tebas. The focus of this study includes: first, how students experience difficulties in performing wudhu in accordance with fiqh teachings at MTs.S Gerpemi Tebas; second, how teachers attempt to overcome students’ difficulties in performing wudhu; and third, the factors causing students’ difficulties in performing wudhu in fiqh learning at MTs.S Gerpemi Tebas. This study employs a qualitative approach with a phenomenological type. Data collection techniques include interviews, observations, and documentation. The validity of the data is ensured through triangulation, prolonged observation, and member checking. Based on the data analysis, the findings show that students’ difficulties in performing wudhu are caused by a lack of knowledge and understanding of the concept of wudhu taught by the teacher. In addition, students’ lack of skills in performing the movements of wudhu, attitudes, and insufficient religious understanding also contribute to their inability to perform wudhu properly and correctly. The teacher’s efforts to overcome these difficulties include demonstrating the correct procedures of wudhu, conducting practical evaluations of wudhu, assisting and paying attention to students during the learning process, and providing guidance and motivation regarding the importance of wudhu in daily life, especially in worship. The factors causing students’ difficulties in performing wudhu consist of internal and external factors. Internal factors include students’ motivation, knowledge, attitudes, and skills in performing wudhu movements. External factors include family, school, and community education, as well as the influence of peers and increasingly advanced technology. A lack of proper religious understanding is also a contributing factor to students’ inability to perform wudhu correctly.